Explaining Unemployment in Spain : Structural Change, Cyclical Fluctuations, and Labor Market Rigidities - Franks, Jeffrey (IMF Working Papers; Working Paper ;, 1994)
Spain has the most serious and persistent unemployment problem in Europe, with an unemployment rate that reached 24.6 percent in early 1994. This paper explores the characteristics of this unemployment problem, its causes, and provides a brief discussion of recent labor market reform measures and their likely Impact. A demographic shift in recent years has produced a large rise in female labor force participation and a decrease in agricultural jobs to which the economy has been unable to adjust. The effects of generous unemployment benefits and the large underground economy may explain 6-12 percentage points of the resulting unemployment, but the remainder must be explained by failures and rigidities in the labor market. The paper presents econometric evidence that unemployment displays hysteresis, and that wages are not responsive to changes in the unemployment rate. This evidence supports the claim that insider-outsider factors and rigidities in the legal structure of the labor market are responsible for much of the high unemployment rate. Recent reforms have improved the functioning of the labor market, but they are unlikely to be sufficient to reduce unemployment to single digit rates without further action.